COVID-19 positive cases among asymptomatic individuals during the second wave in Ndola, Zambia - Jonathan Gwasupika; Victor Daka; Justin Chileshe; Moses Mukosha; Steward Mudenda; Bright Mukanga; Ruth L. Mfune; Gershom Chongwe (AOSIS, 2023)
Background: Coronavirus disease 2019 (COVID-19) is a worldwide public health concern for healthcare workers. About 80% of cases appear to be asymptomatic, and about 3% may experience hospitalisation and later die. Less than 20% of studies have looked at the positivity rate of asymptomatic individuals. Objective: This study investigated the COVID-19 positivity rates among asymptomatic individuals during the second COVID-19 wave at one of Zambia's largest testing centre. Methods: This was a retrospective cross-sectional study conducted on routine surveillance and laboratory data at the Tropical Diseases Research Centre COVID-19 laboratory in Ndola, Zambia, from 01 December 2020 to 31 March 2021. The study population was made up of persons that had tested for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection as a requirement for travel. Microsoft Excel was used to come up with an epidemiological curve of daily COVID-19 positive cases; proportions for gender were described using frequencies and percentages. Results: A total of 11 144 asymptomatic individuals tested for SARS-CoV-2 were sampled for the study and 1781 (16.0%) returned positive results. The median age among those tested was 36 years (interquartile range: 29-46). Testing for COVID-19 peaked in the month of January 2021 (37.4%) and declined in March 2021 (21.0%). The epidemiological curve showed a combination of continuous and propagated point-source transmission. Conclusion: The positivity rate of 16.0% among asymptomatic individuals was high and could imply continued community transmission, especially during January 2021 and February 2021. We recommend heightened testing for SARS-CoV-2 among asymptomatic individuals. What this study adds: This study adds critical knowledge to the transmission of COVID-19 among asymptomatic travellers who are usually a key population in driving community infection. This knowledge is critical in instituting evidence-based interventions in the screening and management of travellers, and its control.